IDENTIFICATION OF ACTIVE COMPOUNDS IN RED ONION (Allium ascalonicum L.) PEEL EXTRACT BY LC-ESI-QTOF-MS/MS AND DETERMINATION OF ITS ANTIOXIDANT ACTIVITY - Maryuni, Dela Retno; Prameswari, Destia Ayu; Astari, Saffarina Dini; Sari, Salsabila Permata; Putri, Desiana Nuriza (Universitas Sebelas Maret (UNS), 2022)
Red onion is one of the foodstuffs that people in everyday life widely use, but 10% of red onion cannot be consumed and only becomes waste, namely the peel of the onion. Although the peel of the onion is a waste, the peel of the onion contains flavonol compounds from the flavonoid group that has the potential as antioxidants. So this study was conducted to determine the compounds in the red onion peel that acts as antioxidants. The extraction method used in this research is the maceration method with 80% ethanol solvent. The compound content test was carried out by testing phytochemical compounds by identifying flavonoid compounds, polyphenols, steroids and terpenoids, saponins, alkaloids, anthocyanins, antioxidant activity, and identification of compounds using LC-MS. The study results on qualitative testing of phytochemical compounds showed that the onion peel extract contained positive flavonoids, polyphenols, and saponins. Meanwhile, the identification of compound content of onion peel extract using LC-MS detected flavonoids (14 compounds), polyphenols (1 compound), saponins (2 compounds), and alkaloids (1 compound). The antioxidant activity of the ethanolic extract of the onion peel has obtained an average of 77%, and the total anthocyanin content was an average of 17.87 mg/L. It was found that the natural antioxidant of onion peel extract showed good primary oxidation inhibition ability. So it can be concluded that onion peel extract is effectively used as a natural antioxidant.